Comparison of ThermoCool® Surround Flow Catheter Versus ThermoCool® Catheter in Achieving Persistent Electrical Isolation of Pulmonary Veins: A Pilot Study. (4th December 2012) - BERTAGLIA, EMANUELE; FASSINI, GAETANO; ANSELMINO, MATTEO; STABILE, GIUSEPPE; GRANDINETTI, GIUSEPPE; SIMONE, ANTONIO DE; CALÒ, LEONARDO; PANDOZI, CLAUDIO; PRATOLA, CLAUDIO; ZOPPO, FRANCO; TONDO, CLAUDIO; IULIANO, ASSUNTA; et al.
<x xml:space="preserve">Abstract</x> Persistent Electrical Isolation of Pulmonary Veins. Introduction: Aim of this study was to compare efficacy and safety of the new ThermoCool Surround Flow® catheter (SFc) versus the ThermoCool® (TCc) in achieving persistent circumferential electrical isolation of the pulmonary veins (PVs) in patients with paroxysmal atrial fibrillation (AF). Methods and Results: This multicenter, randomized, controlled study enrolled patients suffering from paroxysmal AF. Randomization was run in a one‐to‐one fashion between radiofrequency ablation by TCc or SFc. Aim of PVs ablation was documentation of electrical isolation with exit/entrance block recorded on a circular catheter. Among the 106 enrolled patients, 52 (49.0%) were randomized to TCc and 54 (51.0%) to SFc. Total volume of infused saline solution during the procedure was lower in the SFc than in TCc group (752.7 ± 268.6 mL vs 1, 165.9 ± 436.2 mL, P < 0.0001). Number of identified and isolated PVs was similar in the 2 groups. Number of PVs remaining isolated 30 minutes after ablation was higher in the SFc than in TCc group (95.2% vs 90.5%, P < 0.03), mainly driven by acute ablation result in the left PVs (96.1% vs 89.7%, P < 0.04). Complications were seldom and observed only in the TCc group (0% vs 3.84%, P < 0.03). At 6‐month follow‐up SFc patients reported a trend toward less AF recurrences compared to those in the TCc group (22.9% vs 27.0%, P = 0.69). Conclusion: PV isolation by SFc lowered the rate of left PV early reconnections and reduced the volume of infused saline solution while maintaining the safety profile of AF ablation. (J Cardiovasc Electrophysiol, Vol. 24, pp. 269‐273, March 2013)